2017
DOI: 10.1038/srep46740
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Selective Suppression of Mutant Huntingtin in Primary Human Blood Cells

Abstract: Post-transcriptional gene silencing is a promising therapy for the monogenic, autosomal dominant, Huntington’s disease (HD). However, wild-type huntingtin (HTT) has important cellular functions, so the ideal strategy would selectively lower mutant HTT while sparing wild-type. HD patients were genotyped for heterozygosity at three SNP sites, before phasing each SNP allele to wild-type or mutant HTT. Primary ex vivo myeloid cells were isolated from heterozygous patients and transfected with SNP-targeted siRNA, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Three such SNPs have been identified that could be used to treat a majority of patients in Europe and the USA [ 88 ]. A recent study has shown the feasibility of allele selective suppression in HD patient primary ex-vivo myeloid cells when using siRNA to target one of these potential SNPs, although the other SNPs tested did not achieve any allele selectivity [ 89 ]. This was thought to be due to the nucleotide sequence and tertiary structure of the transcript surrounding the base mismatch, and therefore a lower proportion of HD patients have targetable SNPs using this siRNA approach than originally thought.…”
Section: Allele Specificitymentioning
confidence: 99%
“…Three such SNPs have been identified that could be used to treat a majority of patients in Europe and the USA [ 88 ]. A recent study has shown the feasibility of allele selective suppression in HD patient primary ex-vivo myeloid cells when using siRNA to target one of these potential SNPs, although the other SNPs tested did not achieve any allele selectivity [ 89 ]. This was thought to be due to the nucleotide sequence and tertiary structure of the transcript surrounding the base mismatch, and therefore a lower proportion of HD patients have targetable SNPs using this siRNA approach than originally thought.…”
Section: Allele Specificitymentioning
confidence: 99%
“…with some indication of a similar effect in the control cells from healthy individuals 46,49 . Given the roles wtHTT might play in cytoskeleton remodelling, intracellular trafficking and transcription, it is plausible that a yet undescribed role for wtHTT could exist in cells of the innate immune system.…”
mentioning
confidence: 64%
“…Previous data indicated the possibility of a role for wtHTT in cytokine release from monocytes and macrophages, whether they carry the Huntington's disease mutation or not 46,49 . In the present study, the cytokine profiles ex vivo of a large number of macrophage samples from normal, healthy individuals treated with either anti-HTT or scrambled siRNA GeRP-treated were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations